(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The evaluation of the effectiveness of IPCMS allows you to learn about the factors that hinder the effective implementation of its activities, as well as the reasons that reduce the competitiveness of products. Studies of scientists have shown that for today developed methods for assessing individual systems of IPCMS, including quality management systems, food safety management, social responsibility management, environmental management, occupational safety and health management system and, accordingly, their integrated systems. But all these approaches and scientific results have not been generalized in a comprehensive methodology for assessing the effectiveness of IPCMS. The article considers the approaches to the assessment of individual components of the integrated product competitiveness management system and integrated management systems. Based on their generalization and critical analysis, the author’s method of assessing the effectiveness of the integrated management system of competitiveness of enterprise products is proposed. At the first stage of the evaluation of the effectiveness of ISMKP is collecting information about the activities of the components of the system and the factors influencing their effectiveness. The next step is to develop evaluation criteria for each of the components of the ISMCP. Then the calculation of intermediate indicators of efficiency of ISMKP on the basis of the defined criteria is carried out. Then the quantitative result of the assessment is translated into a qualitative one on the basis of a certain integrated indicator of the efficiency of the ISMCP of the enterprise. Depending on the value of the integrated index, it is proposed to distinguish low, medium, high and absolute level of efficiency of the integrated product competitiveness management system, which allows to draw conclusions about the level of system formation and make appropriate management decisions to improve it.